2003
DOI: 10.17660/actahortic.2003.597.19
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils in Some Stachys Species Growing in Hungary

Abstract: The volatile oil compositions of five Stachys species (Stachys officinalis L., St. grandiflora Host., St. byzantina Koch., St. germanica L. and St. sylvatica L.) have been studied using a GC/MS technique. All species gave low yields of oil. From St. officinalis 38 compounds were separated and partly identified, from St. grandiflora 24, St. byzantina 30, St. germanica 29 and St. sylvatica 43. All the samples contained o-ocymene, β-phellandrene, γ-terpinene, linalool, trans-and cis-pinocamphone, βcaryophyllene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…swainsonianeae [8], and S. lavandufolia [9,10] were also reported to be sesquiterpene hydrocarbons. In addition, it was found that some Stachys species contain similar amounts of sesquiterpene hydrocarbons and oxygenated mono-and sesquiterpenes, such as S. byzantina, S. grandiflora and S. sylvatica [11], S. balansae [12], S. alopecuros, S. spinulosa [7], and S. oblique [13]. Our findings were generally similar to the literature results for the major components, with minor differences in the research parameters.…”
supporting
confidence: 90%
“…swainsonianeae [8], and S. lavandufolia [9,10] were also reported to be sesquiterpene hydrocarbons. In addition, it was found that some Stachys species contain similar amounts of sesquiterpene hydrocarbons and oxygenated mono-and sesquiterpenes, such as S. byzantina, S. grandiflora and S. sylvatica [11], S. balansae [12], S. alopecuros, S. spinulosa [7], and S. oblique [13]. Our findings were generally similar to the literature results for the major components, with minor differences in the research parameters.…”
supporting
confidence: 90%
“…annua var. annua had been reported before [16][17][18][19][20][21][22], but there is no literature data for the comparative evaluation of the volatile chemical composition obtained from S. macrantha, S. sylvatica and S. annua ssp. annua var.…”
Section: Discussionmentioning
confidence: 99%
“…Bulgaria, Kosova, Croatia, Italy and Hungary originated S. sylvatica samples were previously studied by different groups and sesquiterpene lactones were reported as the major group of substances at all of the works [16][17][18][19][20][21]. Germacrene D was found to be the major component at Hungary, Kosovo and Italy originated samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germacrene D was the main constituent of the leaf essential oil, but only the third major constituent of the flower essential oil. Phytochemical investigations of this subspecies from Croatia [11] and from different subspecies of S. germanica from the Balkan regions [12][13][14] and from Hungary [15] have been reported. Germacrene D represents the main compound in all the investigated samples, while the other major constituents of our samples are either lacking or are present in very small amounts in the plants of other origins.…”
mentioning
confidence: 98%